Strategi Humas Dalam Membangun Citra Sekolah di MTs Negeri 2 Palembang - Nazarudin, Mgs; Siti Khodijah; Ibrahim, Ibrahim (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to identify the public relations strategies used to build a positive image of MTs Negeri 2 Palembang. The method used in this study is qualitative research with a descriptive qualitative approach. Data collection techniques include observation, interviews, and documentation. Additionally, the data analysis techniques used in this research involve data reduction, data presentation, and verification through triangulation to check the validity of the data. The results of this study indicate that the public relations strategies to maintain the school's image at MTs Negeri 2 Palembang have been effective. These strategies include the Strategy of Publicity, where public relations disseminate information by collaborating with mass media; the Strategy of Persuasion, where public relations persuade the public to change their opinions through various activities; the Strategy of Argumentation, where public relations anticipate negative news by organizing activities; and the Strategy of Image, where public relations create publicity by demonstrating environmental awareness